Blue carbon em solos de manguezais do semiárido: importância, métodos de quantificação e emissão de gases C-CO2. - Nóbrega, Gabriel Nuto (2013)
This work was divided into three chapters and aimed to: 1) Quantify the blue carbon soils stock at Ceará state (NE-Brazil); 2) Evaluate the methods for quantifying soil organic carbon (SOC) in the mangroves; and 3) evaluate the greenhouse gas (CO2 and CH4) emission from mangrove soils. In the first chapter, associations of the phytoecological units (PU) with soil types from Ceará were processed through geoprocessing techniques, combining the information of soil bulk density and carbon content in the soil classes contained in each PU. Results show that the carbon mass in the soils are estimated in 374,123,384.15 Mg. The mangrove contribute to 0.35 % of the carbon mass, since their area does not exceed 0.1% of the state. On the other hand, the carbon stock (CS) data indicate that mangroves store 8241.39 Mg C km-2, equivalent to 3 times the CS mean of the remaining states. This result could be even more important if the mangroves were under less human impact. The second chapter SOC contents were quantified by different chemical (variations in the Walkley & Black), spectral reflectance and thermogravimetric methods and the results were compared with those obtained using elemental analyzer (EA). Regarding chemical analysis, the use of dried samples favored the accuracy of the chemical method, since it promoted the oxidation of the reduced compounds which causes interference. The use of external heating sources resulted in a greater interference in the chemical method and, in a 6M H2SO4 concentration, the chemical method presented viable to quantify COS in mangroves. The spectral reflectance technique showed weak correlations with carbon values obtained by AE, precluding the use of this method and making necessary further studies to the suitability of this method to quantify SOC in mangroves. The results obtained by thermogravimetry showed the strongest correlation with AE (r = 0.927), characterized as the most suitable method for the quantification of SOC, since a correction factor (f = 0.27) is applied for the conversion of soil organic matter values in SOC. In the last chapter, the average CO2 and CH4 flow were quantified and the values were correlated with soil attributes. CO2 fluxes ranged from 16.4 ± 3.7 to 44.4 ± 2.2 mg m-2 h-1. The highest CO2 emission was determined by soil conditions (higher EC, higher concentration of dissolved organic carbon and lower degree of pyritization). The CO2 emissions in mangrove soils corresponds to only 2% of the flow caused by agriculture. The CH4 concentrations were below the detection limit of the equipment used, and thus the average flow of methane cannot be quantified. The low methane flow is related to the abundance of electron acceptors more energetic which prevent methanogenesis and to the presence of microorganisms that oxidize CH4 before it reach the atmosphere.